(untitled) (Fiep Bulletin - online, 2014)
The Karate has been teaching children in general starting from 5 or 6 years, this stage of life is classified as "Sports Initiation". and brings many benefits to practitioners, however the proposed methodology of Kodomo on the Karate addresses to children still minors, that they were neglected in these plans sports, and they can experience a rich psychomotor experience. This study aimed to compare the motor skills of practitioners Kodomo Method in Karate with the skills of kindergarten children from a school in Fortaleza. The sample included 15 children aged Kodomo Method 3-5 years and 15 of the School with the same age group. The research was characterized as quantitative and comparative cross. The research instrument used the Motor Development Scale (EDM) proposed by Rosa Neto. We compared data from subjects who practiced Karate Kodomo Method and dadose presented comoresultados, "Very Superior", "Superior" while the school had "superior", "High Normal" and "Normal Medium", pointing to higher rates first. We conclude that the method Kodomo assists in the development of psychomotor components of the child in this sample.